THE ROLE OF THE MEANING OF IJMÄ€L SURAH AL-FÄ€TIHAH IN FORMULATING EDUCATIONAL INTERPRETATION OF SURAH AL-BAQARAH [2]: 1-20 BASED ON TAZKIYAT AL-NAFS - Itah Miftahul Ulum; Mustopa Mustopa (JURNAL YAQZHAN: Analisis Filsafat, Agama dan Kemanusiaan, 2022)
ABSTRACT: This study analyzes the meaning of ijmÄl in al-FÄtihah with the meaning of ifshÄl in al-Baqarah [2]: 1-20. As for the research problem in this research is how formulation of educational interpretation with a transdisciplinary approach. The research method used is al-tafsÄ«r al-tahlÄ«li which analyzes the relevance of al-FÄtihah [1]: 1-4, 5-6 with al-Baqarah [2]: 1-9; and the relevance of al-FÄtihah [1]: 6-7 with al-Baqarah [2]: 1-20 as a whole until it becomes the original interpretation of researcher. The research findings show, al-FÄtihah [1]: 1-6 contains the meaning of monotheism relating to the themes (1) prayer and infÄq; (2) social interaction between believers, disbelievers and hypocrites; (3) science; (4) education and learning outcomes; (5) propaganda; (6) human ethics and ability to subdue nature; (7) the benefits of al-Quran for believers; and (8) dzikr. The relevance to the meaning of ijmÄl al-FÄtihah [1]: 6-7 with al-Baqarah [2]: 1-20 in formulating educational interpretations is related to the believers who empower their fitrah and reason until they are on the straight path. As for the disbelievers and the hypocrites who are angered by Allah and are heretical because they do not empower their fitrah and reason in understanding ayah qawliyah and ayah kawniyah.